Innovative Practices Connecting Classrooms through Asynchronous and Asynchronous Technology - Prathikantam, Vinayadhar Raju (Indian Journal of Educational Technology, 2021)
The aim of this project was to integrate the technology in low-tech classrooms, particularly in rural government schools. Most of the teachers complain that students studying in rural India are not exposed to enough English so, this innovative practice helps to get connected with the native speakers using technology. During our project, we connected the classroom of the United States (US) with the classroom in India using a technology tool called Pad/et. We made a plan of action for 7 weeks. We designed activities like, introducing each other on the online collaborative wall by posting three sentences, out of those three one is a lie. The students were asked to identify the lie and comment on it. This continued for two weeks. After two weeks they were asked to write a review on a film which they have seen recently and asked to read and comment on at least two or three students. This continued for about two more weeks. During the last two weeks, we worked on a Backpack project. Students were encouraged to read the reports or articles on backpacks and collect the information in their own country's context. After collecting information using the internet they prepared presentations and presented them to their class. Their presentations were recorded and shared with the US students. US students also filmed their presentations and shared with us. We came to the conclusion that the students are engaged meaningfully by integrating technology in the classroom. Students got an opportunity to interact with native speakers. This project also helped us to learn and understand US culture based on the reviews written by them. We also learned that students learn better when they are engaged in collaborative tasks with their peers. Technology played a vital role in our collaboration. Most of my students are not good at using technology but this project made them learn to browse the internet and started using Pad/et effectively.